Multiaxial fatigue behavior and life prediction of 7075-T651 aluminum alloy under two-step loading. (1st May 2020) - Chen, Yajun; Xu, Pengda; Liu, Chenchen; Wang, Fusheng; Song, Haipeng
Highlights: Constant amplitude & two-step loading spectra multiaxial fatigue tests on AA7075-T651. Fatigue damage accumulation rate is decreased by the two-step loading interaction. Loading step corresponding to lower fatigue life dominates in two-step loading spectra. A non-linear accumulative damage model based on modified Basquin's criterion. Abstract: Focusing on the loading sequential effects on the multiaxial fatigue damage accumulation, tests including two series of constant amplitude loadings and 12 groups of two-step loading spectra were conducted on 7075-T651 aluminum alloy. Under the same equivalent stress amplitude, the multiaxial fatigue life raises with the increase of stress amplitude ratio. Fatigue damage accumulation rate is decreased by the two-step loading interaction. Cyclic loading curves and fracture morphology analysis reveal that the loading step corresponding to lower fatigue life is dominant. Considering the stress amplitude ratio effects and loading interaction, a non-linear accumulative damage model is proposed based on the modified Basquin's criterion. The proposed model provides a more accurate calculation of accumulative fatigue damage compared with the other four commonly used models. Fine life prediction results are obtained by the proposed model with all predicted data within a factor of three.